Implementing COVID-19 (SARS-CoV-2) Rapid Diagnostic Tests in Sub-Saharan Africa: A Review - Jacobs, Jan; Kühne, Vera; Lunguya, Octavie; Affolabi, Dissou; Hardy, Liselotte; Vandenberg, Olivier (Frontiers in Medicine, 2020)
Introduction: For the COVID-19 (SARS-CoV-2) response, COVID-19 antigen (Ag), and antibody (Ab) rapid diagnostic tests (RDTs) are expected to complement central molecular testing particularly in low-resource settings. The present review assesses requirements for implementation of COVID-19 RDTs in sub-Saharan Africa. Methods: Review of PubMed-published articles assessing COVID-19 RDTs complemented with Instructions for Use (IFU) of products. Results: In total 47 articles on two COVID-19 Ag RDTs and 54 COVID-19 Ab RDTs and IFUs of 20 COVID-19 Ab RDTs were retrieved. Only five COVID-19 Ab RDTs (9.3%) were assessed with capillary blood sampling at the point-of-care; none of the studies were conducted in sub-Saharan Africa. Sampling: Challenges for COVID-19 Ag RDTs include nasopharyngeal sampling (technique, biosafety) and sample stability; for COVID-19 Ab RDTs equivalence of whole blood vs. plasma/serum needs further validation (assessed for only eight (14.8%) products). Sensitivity—Specificity: sensitivity of COVID-19 Ag and Ab RDTs depend on viral load (antigen) and timeframe (antibody), respectively; COVID-19 Ab tests have lower sensitivity compared to laboratory test platforms and the kinetics of IgM and IgG are very similar. Reported specificity was high but has not yet been assessed against tropical pathogens. Kit configuration: For COVID-19 Ag RDTs, flocked swabs should be added to the kit; for COVID-19 Ab RDTs, finger prick sampling materials, transfer devices, and controls should be added (currently only supplied in 15, 5, and 1/20 products). Usability and Robustness: some COVID-19 Ab RDTs showed high proportions of faint lines (>40%) or invalid results (>20%). Shortcomings were reported for buffer vials (spills, air bubbles) and their instructions for use. Stability: storage temperature was ≤ 30°C for all but one RDT, in-use and result stability were maximal at 1 h and 30 min, respectively. Integration in the healthcare setting requires a target product profile, landscape overview of technologies, certified manufacturing capacity, a sustainable market, and a stringent but timely regulation. In-country deployment depends on integration in the national laboratory network. Discussion/Conclusion: Despite these limitations, successful implementation models in triage, contact tracing, and surveillance have been proposed, in particular for COVID-19 Ab RDTs. Valuable experience is available from implementation of other disease-specific RDTs in sub-Saharan Africa.